Answer:
(f•g)(4) = 45
Step-by-step explanation:
f(x)=4x+1
g(x)=x^2-5
(f•g)(x) = 4(x^2 -5)+1
(f•g)(4) = 4(4^2 -5)+1
(f•g)(4) = 4(16-5)+1
(f•g)(4) = 4(11)+1
(f•g)(4) = 44 + 1
(f•g)(4) = 45
Answer:
g(x) = 1/2*(4)^(–x) and
g(x) =1/2*(1/4)^(x)
Please, see attached picture.
Step-by-step explanation:
Your full question is attached in the picture below
To easily solve this problem, we can graph each equation and see, which one represents a reflection of the function over the y axis.
See, second image.
The answers are
g(x) = 1/2*(4)^(–x) and
g(x) =1/2*(1/4)^(x)
A pipe that carries water
Answer: last one
Step-by-step explanation:
Answer:
11x-8
Step-by-step explanation: